PREDICTABILITY AND ACCESSIBILITY OF THE LAW - Elena ANGHEL (Challenges of the Knowledge Society)
„Where the force of the laws and the authority of their defenders cease, there can be neither liberty nor safety for any," wrote Shakespeare. The rule of law presupposes the obligation to respect the Constitution and the laws, as provided by the provisions of art. 1 para. (5) of the Constitution. In order for the law to be accepted and respected, it must present a certain legal security, assuming the requirements of accessibility and predictability, logical coherence and stability, features designed to capture the trust of citizens in its provisions. The need to match laws with time and not time with laws has been emphasized since antiquity. But, as we will show in the present study, the belief in the perfectibility of the law was gradually deprived of rights. The lack of accessibility and predictability of legal provisions is increasingly invoked before the Constitutional Court, which ruled, in numerous cases, on the violation of these requirements, by reference to the ECtHR jurisprudence, as the existence of interpretation problems and law enforcement is inherent in any legal system, given the fact that, inevitably, legal norms have a certain degree of generality. As the Constitutional Court ruled in its jurisprudence, the obligation to respect the laws does not imply, by its content, the provision of an inflexible legislative framework. Legislative intervention is necessary both to adapt the normative acts to the existing economic, social and political realities, but also to ensure a unitary legislative framework, which contributes to a better application of the law and to the removal of any ambiguous situations or inequities in the application of the law.